Activities of the Japanese Arctic Glaciological Expedition in 1998 (JAGE 1998) - WATANABE, Okitsugu; KAMIYAMA, Kokichi; KAMEDA, Takao; TAKAHASHI, Shuhei; ISAKSSON, Elisabeth
The prime objective of the Japanese Arctic Glaciological Expedition (JAGE) is to study the climatic and environmental changes for the last few hundred years using ice cores from various areas of the Arctic cryosphere. Ice coring down to 118.48m and ice core analyses in situ, as well as the meteorological observation, were carried out at the top of Austfonna (Austdomen) in Nordaustlandet, Svalbard, from 9 March to 20 April 1998. Some heavy equipment and fuel for the helicopter were carried to the coastal area of Nordaustlandet by Lance, the research vessel of Norwegian Polar Institute, during the summer season of 1997. A total of 3.24 tons of equipment was transported to the ice-coring site by a helicopter in the spring season of 1998. It took 20.23 hours for the total helicopter operation. Five members stayed on Austfonna from 9 to 27 March and four members stayed from 27 March to 20 April. application/pdf journal article